2020
DOI: 10.3389/fpubh.2020.608718
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Exposure and Workplace Measurements During Processes Related to 3D Printing of a Metal Object

Abstract: Metal 3D printing has many potential uses within prototyping and manufacturing. Selective laser melting (SLM) is a process that uses metal powders in the micrometer range as printing material. The particle release from the entire SLM printing process is not well-studied. While the 3D printing itself often occurs in a sealed chamber, activities related to the process can potentially release harmful metal particles to the indoor working environment through resuspension of the printing powder or via incident nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Occupational incidental nanoparticles usually originated from industrial processes that require high temperature or massive energy [4], such as metal additive manufacturing, which uses, for example, electron beams and lasers as heat sources. Recent studies have been published on this topic, showing the importance of studying the occupational risk of exposure to UFPs in metal AM workstations [7][8][9]. Some metal-based nanoparticles can cause adverse effects at cellular and subcellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational incidental nanoparticles usually originated from industrial processes that require high temperature or massive energy [4], such as metal additive manufacturing, which uses, for example, electron beams and lasers as heat sources. Recent studies have been published on this topic, showing the importance of studying the occupational risk of exposure to UFPs in metal AM workstations [7][8][9]. Some metal-based nanoparticles can cause adverse effects at cellular and subcellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…The inhalation exposure potential for solid-based processes can occur when feedstock powders and filaments are used in an area with minimal ventilation . VOC concentrations of 0.02–0.13 mg/m 3 (C exposure,disposal ) have been reported from solid material processing . Therefore, EXP inhalation may range from 0.2 to 1.3 mg/day/operator for solid disposal.…”
Section: Resultsmentioning
confidence: 99%
“…In the Jensen et al study, the number of particles identified in the various phases of metal 3D printing (SLM -Selective laser melting) ranged from 5×10 3 to 2.5×10 5 particles/cm 3 . [46]. In another study the most popular filaments of 3D printers (ABS, PLA) were tested and the particles they issue.…”
Section: Discussionmentioning
confidence: 99%